High-strength vehicle tarpaulin and preparation method thereof

By introducing multi-layer structures and specific additives into PVC vehicle tarpaulins, the problem of insufficient tarpaulin strength is solved, and the effects of high strength and high peel strength are achieved, ensuring the safety of goods during transportation.

CN120269900APending Publication Date: 2025-07-08SHIJIAZHUANG WISE TRADING CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510658932.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-21
Publication Date
2025-07-08

AI Technical Summary

Technical Problem

The existing PVC vehicle tarpaulin is insufficient in strength and is easily scratched or torn by the cargo during vibration and bumps, resulting in the cargo being eroded.

Method used

A multi-layer structure consisting of the first PVC layer, a base cloth layer, and a second PVC layer is adopted. The base cloth layer material is a glass fiber mesh cloth or a polyester fiber mesh cloth. An adhesive layer is used between the layers, and polyethylene lactone diol, composite titanium dioxide and other substances are added to improve strength and compatibility, and a high-strength tarpaulin is formed by hot pressing bonding.

Benefits of technology

It significantly improves the tear resistance and peel strength of the tarpaulin, enhances the overall mechanical properties of the tarpaulin, and ensures the integrity of the cargo during transportation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of tarpaulin, and provides high-strength vehicle tarpaulin and a preparation method thereof.The high-strength vehicle tarpaulin comprises a first PVC layer, a base cloth layer and a second PVC layer which are sequentially arranged from bottom to top, a first adhesive layer is arranged between the first PVC layer and the base cloth layer, and a second adhesive layer is arranged between the second PVC layer and the base cloth layer; the material of the base cloth layer comprises one of glass fiber gridding cloth, polyester fiber gridding cloth and PVC gridding cloth, and the materials of the first PVC layer and the second PVC layer respectively and independently comprise the following raw materials in parts by weight: 100 parts of PVC resin, 15-20 parts of a first plasticizer, 20-30 parts of calcium powder, 5-8 parts of titanium dioxide, 2-3 parts of a stabilizer and 5-10 parts of polycaprolactone glycol. By means of the technical scheme, the problem that in the related technology, the strength of the vehicle tarpaulin is low is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field, and specifically, to a high-strength vehicle tarpaulin and a preparation method thereof. Background Art

[0002] The PVC vehicle tarpaulin includes a base layer, a PVC layer and an adhesive layer. The PVC material has the characteristics of low cost and good waterproof performance. During the driving of the vehicle, vibrations will occur, and it may encounter bumpy roads. The vehicle tarpaulin will bear the impact force generated by the vibration and collision of the goods in the vehicle. If the strength of the vehicle tarpaulin is insufficient, the tarpaulin will be cut or torn by the goods, resulting in the goods being eroded by rain, dust, etc. Therefore, in order to ensure the integrity of the goods during transportation, it is necessary to improve the strength of the PVC vehicle tarpaulin. Summary of the Invention

[0003] The present invention provides a high-strength vehicle tarpaulin and a preparation method thereof, which solves the problem of low strength of the vehicle tarpaulin in the related art.

[0004] The technical solution of the present invention is as follows: The present invention provides a high-strength vehicle tarpaulin, which includes a first PVC layer, a base fabric layer and a second PVC layer arranged in sequence from bottom to top. A first adhesive layer is arranged between the first PVC layer and the base fabric layer, and a second adhesive layer is arranged between the second PVC layer and the base fabric layer. The material of the base fabric layer includes one of fiberglass mesh cloth and polyester fiber mesh cloth. The materials of the first PVC layer and the second PVC layer each independently include raw materials with the following weight parts: 100 parts of PVC resin, 15 - 20 parts of a first plasticizer, 20 - 30 parts of calcium powder, 5 - 8 parts of titanium dioxide, 2 - 3 parts of a stabilizer, and 5 - 10 parts of polycaprolactone diol.

[0005] As a further technical solution, the stabilizer includes one or more of calcium stearate, zinc stearate, and magnesium stearate.

[0006] During the processing and use of the tarpaulin, it will be affected by heat, light, etc., resulting in the destruction and degradation of the PVC molecular structure, forming microscopic defects inside, and causing the strength of the tarpaulin to decrease. The addition of the stabilizer can maintain the structural integrity of the PVC molecular chain and maintain the strength of the tarpaulin.

[0007] As a further technical solution, the calcium powder includes one of light calcium carbonate and heavy calcium carbonate.

[0008] As a further technical solution, the thicknesses of the first adhesive layer and the second adhesive layer are each independently 0.04 - 0.06 mm.

[0009] As a further technical solution, the thicknesses of the first PVC layer and the second PVC layer are independently 0.3 to 0.4 mm.

[0010] As a further technical solution, the thickness of the base fabric layer is 0.2 to 0.3 mm.

[0011] As a further technical solution, the weight-average molecular weight of the polycaprolactone diol is 530 to 2000.

[0012] As a further technical solution, the polycaprolactone diol is composed of a first polycaprolactone diol and a second polycaprolactone diol, and the weight-average molecular weights of the first polycaprolactone diol and the second polycaprolactone diol are different.

[0013] As a further technical solution, the weight-average molecular weight of the first polycaprolactone diol is 830, the weight-average molecular weight of the second polycaprolactone diol is 2000, and the addition amount of the first polycaprolactone diol is greater than the addition amount of the second polycaprolactone diol.

[0014] The present invention finds that the addition of polycaprolactone diol can not only improve the strength of the vehicle tarpaulin, but also, on the basis of adding polycaprolactone diol, the compounding of polycaprolactone diols with different weight-average molecular weights can better improve the peel strength of the tarpaulin. The present invention defines that the weight-average molecular weight of the first polycaprolactone diol is 830 and the weight-average molecular weight of the second polycaprolactone diol is 2000. During the preparation process, the low weight-average molecular weight polycaprolactone diol can be filled in the gaps between PVC molecules, and can also make the high weight-average molecular weight polycaprolactone diol better dispersed and entangled with PVC molecules, strengthening the overall mechanical properties. The high weight-average molecular weight polycaprolactone diol can provide a stable network structure for the low weight-average molecular weight polycaprolactone diol. Through the synergistic effect of the interweaving of the low weight-average molecular weight polycaprolactone diol and the high weight-average molecular weight polycaprolactone diol, the strength of the tarpaulin can be further improved.

[0015] As a further technical solution, the mass ratio of the first adhesive layer and the second adhesive layer is 4:1 to 2.

[0016] In the present invention, the limitation of the ratio of the first polycaprolactone diol and the second polycaprolactone diol with different weight-average molecular weights can give full play to their synergistic effect and further improve the strength of the tarpaulin.

[0017] As a further technical solution, the raw materials of the first adhesive layer and the second adhesive layer independently include the following raw materials in parts by weight: 100 parts of PVC paste resin, 20 to 30 parts of a second plasticizer, 15 to 20 parts of titanium dioxide, 2 to 3 parts of an antioxidant, and 70 to 80 parts of an organic solvent.

[0018] As a further technical solution, the titanium dioxide is composite titanium dioxide, and the composite titanium dioxide includes nano-titanium dioxide and amino compounds. The amino compounds include one or more of methyl p-aminobenzoate, methyl 4-amino-3-carbamoylbenzoate, and ethyl 3-amino-2,4-diaminomethylbenzoate, preferably methyl 4-amino-3-carbamoylbenzoate.

[0019] In the present invention, the compatibility between the added titanium dioxide and PVC paste resin is poor, and the titanium dioxide itself has the problem of easy agglomeration. Therefore, after the titanium dioxide is subjected to composite modification, the problems of easy agglomeration and poor compatibility can be solved. Moreover, since the PVC layer contains calcium powder and titanium dioxide, after the tarpaulin is hot-pressed and compounded, the addition of the composite titanium dioxide can also improve the peel strength of the tarpaulin.

[0020] In the present invention, the selection of amino compounds has a certain influence on the peel strength of the tarpaulin. Compared with the selection of methyl 4-amino-3-carbamoylbenzoate as the amino compound, the peel strength of the tarpaulin can be further improved, and the peel strength can be as high as 103 N.

[0021] As a further technical solution, the preparation method of the composite titanium dioxide includes the following steps: adding nano-titanium dioxide into a solution and dispersing it evenly, then adding amino compounds for improvement, and drying to obtain the composite titanium dioxide.

[0022] As a further technical solution, the amino compound is 3% - 5% of the mass of the nano-titanium dioxide, preferably 4%.

[0023] As a further technical solution, the modification temperature is 30 - 50 °C, preferably 40 °C, and the modification time is 1 - 3 h, preferably 2 h.

[0024] As a further technical solution, the antioxidant includes one or more of antioxidant 1010, antioxidant 1076, and antioxidant 168.

[0025] During the processing of PVC paste resin in the PVC slurry, it will be heated. At high temperatures, its molecular chains are unstable and are prone to generating free radicals under the action of oxygen. These free radicals will initiate chain reactions, resulting in the breakage and cross-linking of resin molecular chains, etc., and reducing the performance of the PVC paste resin. The addition of antioxidants can capture these free radicals generated under the action of oxygen, terminate the chain reaction, and maintain a high bonding performance.

[0026] As a further technical solution, the PVC paste resin includes one or more of PR-457, PR-450, BPR-440, and BPR-450. The degree of polymerization of PR-457 is 800±100, the degree of polymerization of PR-450 is 1000±100, the degree of polymerization of BPR-440 is 1450±200, and the degree of polymerization of BPR-450 is 1000±1000. Preferably, they are PR-450, BPR-440, and BPR-450, and more preferably BPR-440.

[0027] As a further technical solution, the organic solvent is cyclohexanone.

[0028] As a further technical solution, each of the first plasticizer and the second plasticizer independently includes one or more of dioctyl phthalate, diisononyl phthalate, and dioctyl terephthalate.

[0029] In the present invention, adding a plasticizer to the PVC resin can improve the intermolecular force and enhance the strength of the PVC resin. Adding a plasticizer to the PVC paste resin can improve the fluidity, fully contact the surface of the PVC layer and the base fabric layer, and increase the peel strength between the PVC layer and the base fabric layer.

[0030] The present invention also provides a method for preparing a high-strength vehicle tarpaulin for preparing the high-strength vehicle tarpaulin, which includes the following steps: hot pressing and bonding in the order of a first PVC layer, a first adhesive layer, a base fabric layer, a second adhesive layer, and a second PVC layer from bottom to top to obtain the high-strength vehicle tarpaulin.

[0031] The working principle and beneficial effects of the present invention are as follows: In the present invention, the PVC layer and the base layer are bonded with a PVC slurry. The main components of the PVC slurry are the same as those of the PVC layer. Therefore, the PVC slurry has good compatibility with the PVC layer and has a good bonding effect compared with other adhesives. Moreover, polycaprolactone diol is added to the PVC layer. The addition of polycaprolactone diol can not only improve the compatibility of calcium powder, titanium dioxide and PVC resin in the PVC layer, make the calcium powder and titanium dioxide more evenly distributed in the PVC layer, but also improve the strength of the PVC vehicle tarpaulin. Specific embodiments

[0032] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts fall within the scope of protection of the present invention.

[0033] In the following examples and comparative examples: The material of the base fabric layer is: PVC mesh fabric, with a thickness of 0.3 mm and a 1 cm mesh; PVC paste resin: Model BPR-440, Corning Chemical; PVC resin: S-65, Formosa Plastics Ningbo; Nano-titanium dioxide: average particle size of 50 nm; Light calcium carbonate: average particle size of 1250 mesh; Titanium dioxide: average particle size of 1250 mesh.

[0034] Example 1 A preparation method of a high-strength vehicle tarpaulin, comprising the following steps: S1. Mix 100 parts of PVC resin, 15 parts of dioctyl phthalate, 20 parts of light calcium carbonate, 5 parts of titanium dioxide, 2 parts of calcium stearate, and 5 parts of polycaprolactone diol, and after kneading, extrusion, and calendering, obtain a PVC film with a thickness of 0.3 mm; wherein the weight-average molecular weight of polycaprolactone diol is 830; S2. Mix 100 parts of PVC paste resin, 20 parts of dioctyl phthalate, 15 parts of nano-titanium dioxide, 2 parts of antioxidant 1010, and 70 parts of cyclohexanone evenly to obtain a PVC slurry; S3. After coating the first adhesive layer on the upper surface of the first PVC layer (coating thickness is 0.04 mm) and the lower surface of the second PVC layer (coating thickness is 0.04 mm) respectively, perform hot pressing and bonding in the order of the first PVC layer, the first adhesive layer, the base fabric layer, the second adhesive layer, and the second PVC layer from bottom to top to obtain a high-strength vehicle tarpaulin; the materials of the first adhesive layer and the second adhesive layer are both the PVC slurry prepared in S2, and the materials of the first PVC layer and the second PVC layer are both PVC films with a thickness of 0.3 mm.

[0035] Example 2 A preparation method of a high-strength vehicle tarpaulin, comprising the following steps: S1. Mix 100 parts of PVC resin, 20 parts of dioctyl phthalate, 30 parts of light calcium carbonate, 8 parts of titanium dioxide, 3 parts of calcium stearate, and 10 parts of polycaprolactone diol, and after kneading, extrusion, and calendering, obtain a PVC film with a thickness of 0.4 mm; wherein the weight-average molecular weight of polycaprolactone diol is 830; S2. Mix 100 parts of PVC paste resin, 30 parts of dioctyl phthalate, 20 parts of nano-titanium dioxide, 3 parts of antioxidant 1010, and 80 parts of cyclohexanone evenly to obtain a PVC slurry; S3. After the first adhesive layer is coated on the upper surface of the first PVC layer (coating thickness: 0.06 mm) and the lower surface of the second PVC layer (coating thickness: 0.06 mm) respectively, hot pressing and bonding are carried out in the order of the first PVC layer, the first adhesive layer, the base fabric layer, the second adhesive layer, and the second PVC layer from bottom to top to obtain a high-strength vehicle tarpaulin; the materials of the first adhesive layer and the second adhesive layer are both the PVC slurry prepared in S2, and the materials of the first PVC layer and the second PVC layer are both PVC films with a thickness of 0.4 mm.

[0036] Example 3 Compared with Example 1, the difference in Example 3 is only that the weight-average molecular weight of polycaprolactone diol is 2000.

[0037] Example 4 Compared with Example 1, the difference in Example 4 is only that the polycaprolactone diol is composed of a first polycaprolactone diol (weight-average molecular weight: 830) and a second polycaprolactone diol (weight-average molecular weight: 2000) with a mass ratio of 4:1.5.

[0038] Example 5 Compared with Example 1, the difference in Example 5 is only that the polycaprolactone diol is composed of a first polycaprolactone diol (weight-average molecular weight: 530) and a second polycaprolactone diol (weight-average molecular weight: 2000) with a mass ratio of 4:1.5.

[0039] Example 6 Compared with Example 1, the difference in Example 6 is only that the polycaprolactone diol is composed of a first polycaprolactone diol (weight-average molecular weight: 830) and a second polycaprolactone diol (weight-average molecular weight: 3000) with a mass ratio of 4:1.5.

[0040] Example 7 Compared with Example 6, the difference in Example 7 is only that in Example 7, the titanium dioxide in the PVC slurry is composite titanium dioxide, and the preparation method of the composite titanium dioxide includes the following steps: 40 parts of nano titanium dioxide are added to 300 parts of absolute ethanol and dispersed evenly, then 1.6 parts of methyl p-aminobenzoate are added and modified at 40°C for 2 h, and then dried to obtain the composite titanium dioxide.

[0041] Example 8 Compared with Example 7, the difference in Example 8 is only that methyl p-aminobenzoate is replaced with an equal amount of methyl 4-amino-3-aminocarbonylbenzoate.

[0042] Example 9 Compared with Example 7, the difference in Example 9 is only that methyl p-aminobenzoate is replaced with an equal amount of ethyl 3-amino-2,4-diaminomethylbenzoate.

[0043] Example 10 Compared with Example 8, Example 10 is only different in that 1.2 parts of methyl 4-amino-3-carbamoylbenzoate are used.

[0044] Example 11 Compared with Example 8, Example 11 is only different in that 2 parts of methyl 4-amino-3-carbamoylbenzoate are used.

[0045] Comparative Example 1 Compared with Example 1, Comparative Example 1 is only different in that polycaprolactone diol (weight average molecular weight of 830) is not added.

[0046] Experimental Example The tear resistance and peel strength of the vehicle tarpaulins in Examples 1 to 9 and Comparative Example 1 were measured. The measurement methods are as follows: (1) Tear resistance: The longitudinal tear strength of the tarpaulin was measured according to the measurement method in DIN 53363; (2) Peel strength: The peel strength of the tarpaulin was measured according to the measurement method in FZ / T 60039; (3) Migration resistance: The migration rate of the tarpaulin was measured by the weight loss method. The test conditions were: 65 °C, 30 d; The measurement results are shown in Tables 1 to 3.

[0047] Table 1 Performance measurement results of vehicle tarpaulins in Examples 1 to 6 and Comparative Example 1

[0048] As can be seen from Table 1, the tear strength of the tarpaulins in Examples 1 to 6 of the present invention is as high as 846 - 935 N, showing good tear resistance.

[0049] Table 2 Performance measurement results of vehicle tarpaulins in Examples 6 to 11

[0050] As can be seen from Table 2, the highest peel strength of the vehicle tarpaulin of the present invention can reach 105 N. The addition of composite titanium dioxide can improve the glass strength of the tarpaulin.

[0051] Table 3 Measurement of the migration performance of the vehicle tarpaulin in Example 1

[0052] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high-strength vehicle tarpaulin, characterized in that, It includes a first PVC layer, a base fabric layer, and a second PVC layer arranged from bottom to top. A first adhesive layer is provided between the first PVC layer and the base fabric layer, and a second adhesive layer is provided between the second PVC layer and the base fabric layer. The material of the base fabric layer includes one of fiberglass mesh cloth, polyester fiber mesh cloth, and PVC mesh cloth. The raw materials of the first adhesive layer and the second adhesive layer are both PVC slurry. The materials of the first PVC layer and the second PVC layer each independently include raw materials with the following weight parts: 100 parts of PVC resin, 15 - 20 parts of a first plasticizer, 20 - 30 parts of calcium powder, 5 - 8 parts of titanium dioxide, 2 - 3 parts of stabilizer, and 5 - 10 parts of polycaprolactone diol.

2. The high-strength vehicle tarpaulin according to claim 1, wherein The thicknesses of the first adhesive layer and the second adhesive layer each independently are 0.04 - 0.06 mm.

3. The high-strength vehicle tarpaulin according to claim 1, wherein The thicknesses of the first PVC layer and the first PVC layer each independently are 0.3 - 0.4 mm.

4. The high-strength vehicle tarpaulin according to claim 1, characterized in that, The thickness of the base fabric layer is 0.2 - 0.3 mm.

5. A high-strength vehicle tarpaulin according to claim 1, characterized in that The raw materials of the first adhesive layer and the second adhesive layer each independently include raw materials with the following weight parts: 100 parts of PVC paste resin, 20 - 30 parts of a second plasticizer, 15 - 20 parts of titanium dioxide, 2 - 3 parts of antioxidant, and 70 - 80 parts of organic solvent.

6. The high-strength vehicle tarpaulin according to claim 1, wherein The weight average molecular weight of the polycaprolactone diol is 530 - 2000.

7. The high-strength vehicle tarpaulin according to claim 5, wherein, The titanium dioxide is composite titanium dioxide, and the composite titanium dioxide includes nano - titanium dioxide and amino - containing compounds. The amino - containing compounds include one or more of methyl p - aminobenzoate, methyl 4 - amino - 3 - aminocarbonylbenzoate, and ethyl 3 - amino - 2,4 - diaminomethylbenzoate.

8. The high-strength vehicle tarpaulin according to claim 7, wherein, The preparation method of the composite titanium dioxide includes the following steps: After adding nano - titanium dioxide into a solution and dispersing it evenly, add amino - containing compounds for modification, and then dry to obtain the composite titanium dioxide.

9. The high-strength vehicle tarpaulin according to claim 5, characterized in that, The first plasticizer and the second plasticizer each independently include one or more of dioctyl phthalate, diisononyl phthalate, and dioctyl terephthalate.

10. A preparation method of a high-strength vehicle tarpaulin for preparing a high-strength vehicle tarpaulin according to any one of claims 1 to 9, characterized in that, It includes the following steps: Perform hot - press bonding in the order of the first PVC layer, the first adhesive layer, the base fabric layer, the second adhesive layer, and the second PVC layer from bottom to top to obtain a high - strength vehicle tarpaulin.

Citation Information

Patent Citations

  • Degradable PVC plastic

    CN109161128A

  • Online modified PPC resin and preparation process thereof

    CN110563917A

  • Tarpaulin material and preparation method thereof

    CN111959076A

  • Ultraviolet-resistant photovoltaic cable

    CN119331322A

  • Tear-resistant PVC (polyvinyl chloride) composite vehicle tarpaulin, equipment, preparation method and application

    CN119567680A